FOOD CURES : BREAKTHROUGH NUTRITIONAL PRESCRIPTIONS FOR EVERYTHING FROM COLDS TO CANCER - Russell, Elaine, editor; Reader's Digest (Australia) 554782 (Sydney : Reader's Digest (Australia), 2009)
Includes bibliographical and references